Myrtilla Miner papers - Miner, Myrtilla, 1815-1864.
Correspondence, school essays, notes, clippings, printed matter, and other papers relating to the Normal School for Colored Girls (Washington, D.C.), the Civil War, feminism, slavery, and spiritualism. Includes an unfinished biography of Miner written by Lester Grosvenor Wells and correspondence of Achsa Miner and other Miner (Minor) family members. Other correspondents include William H. Beecher, Walpole Cecil, Samuel Rhoads, Emma Dorothy Eliza Nevitte Southworth, Harriet Beecher Stowe, and Benjamin Tatham.
Microfilm edition available
Microfilm produced from originals, photocopies, and transcripts in the Manuscript Division.
In part, photocopies and transcripts.
Educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beecher, William H. -- 1802-1889 -- Correspondence; Cecil, Walpole, -- approximately 1836- -- Correspondence; Miner, Achsa -- Correspondence; Rhoads, Samuel, -- 1806-1868 -- Correspondence; Southworth, Emma Dorothy Eliza Nevitte, -- 1819-1899 -- Correspondence; Stowe, Harriet Beecher, -- 1811-1896 -- Correspondence; Tatham, Benjamin -- Correspondence; Wells, Lester Grosvenor; Minor family -- Correspondence; Normal School for Colored Girls (Washington, D.C.); African Americans -- Washington (D.C.); Education -- Washington (D.C.); Feminism; Slavery -- United States; Spiritualism; United States -- History -- Civil War, 1861-1865.; Educators